The Use of Renewable Energy Sources as The Basis For Sustainable Development: A Case Study - Małgorzata DĄBROWSKA–ŚWIDER; Krzysztof ŚWIDER (Communications of International Proceedings, 2021)
The aim of the article is to present the potential of renewable resources in the context of using them to stop the progressive degradation of the natural environment against the background of activities undertaken by the European Union and on the example of Greater Poland Voivodeship, which showing how the pilot program using renewable energy sources was implemented.
Keywords: Renewable Energy Sources; Ecological Security; Environmental Protection; European Green Order.